2023
DOI: 10.35848/1882-0786/acbe26
|View full text |Cite
|
Sign up to set email alerts
|

The incorporation of AlScN ferroelectric gate dielectric in AlGaN/GaN-HEMT with polarization-modulated threshold voltage

Abstract: In this work, the insertion of AlScN ferroelectric gate dielectric on the performance of AlGaN/GaN HEMT device is investigated. With negative pre-poling on AlScN, the threshold voltage (Vth) of the device shifts positively with a swing range of 3.26 V. The influence of polarization modulation is also reflected by the suppression of gate leakage and the reduction of subthreshold swing of the device. The AlScN-integrated GaN HEMT exhibits on/off ratio of 106 and a subthreshold swing of 80 mV/dec. The depletion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…6,15 Knowing the correct polarity of the polarizations is very important for modeling polarization reversal in GaN-based heterostructures, such as ferroelectric high electron mobility transistors (FeHEMTs). [19][20][21][22] This is due to the fact that different polarities can result in the prediction of different signs of the interface sheet charges and, in consequence, in the sign of accumulated charge carriers that form the channel of the transistor.…”
Section: Modeling Of Polarization Reversal-induced Interface Sheet Ch...mentioning
confidence: 99%
“…6,15 Knowing the correct polarity of the polarizations is very important for modeling polarization reversal in GaN-based heterostructures, such as ferroelectric high electron mobility transistors (FeHEMTs). [19][20][21][22] This is due to the fact that different polarities can result in the prediction of different signs of the interface sheet charges and, in consequence, in the sign of accumulated charge carriers that form the channel of the transistor.…”
Section: Modeling Of Polarization Reversal-induced Interface Sheet Ch...mentioning
confidence: 99%
“…The directions of the electric dipoles are reorganized with ferroelectric domains well aligned with each other. When the 2DEG is partially depleted, the threshold voltage in HEMT will shift positive towards an enhancement-mode HEMT [161]. Following this idea, Zhu et al [162] reported a HEMT-PD incorporated with PZT/ZnO composite ferroelectric and realized UV responsivity larger than 110 W A −1 at 365 nm.…”
Section: Hemt Hybrid Uv-pdmentioning
confidence: 99%
“…[ 1,2 ] They are characterized by some of the largest spontaneous polarizations and coercive fields among ferroelectrics in general, extreme temperature stability, as well as compatibility to the major Si and GaN‐based semiconductor platforms. [ 3–7 ] The fact that the wurtzite‐type ferroelectrics share the same crystal structure and are most often III‐nitrides themselves offers the perspective of introducing novel heterostructures with a sort of native ferroelectricity to engineer novel GaN‐based devices. One of the first devices considered in this context is the ferroelectric high electron mobility transistor (FE‐HEMT), [ 5–8 ] which could ultimately allow reconfigurable normally‐off functionality in normally‐on devices.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3–7 ] The fact that the wurtzite‐type ferroelectrics share the same crystal structure and are most often III‐nitrides themselves offers the perspective of introducing novel heterostructures with a sort of native ferroelectricity to engineer novel GaN‐based devices. One of the first devices considered in this context is the ferroelectric high electron mobility transistor (FE‐HEMT), [ 5–8 ] which could ultimately allow reconfigurable normally‐off functionality in normally‐on devices. Due to economic benefits like high yield and ease‐of‐operation as well as very good single crystal quality, metal organic chemical vapor deposition (MOCVD) is today the dominant method for III‐nitride‐based HEMT fabrication.…”
Section: Introductionmentioning
confidence: 99%